Pengembangan Media Edukasi Berbasis Vidio Untuk Peningkatan Kompetensi Kader Posyandu dalam Mendukung Desa Cantik di Lembar Selatan - Istiqamah, Istiqamah; Baskara, Zulhan Widya; Harsyiah, Lisa; Putri, Dina Eka; Andriani, Helmina; Qudsi, Jihadil; Saputri, Intan Editia (Puslitbang Sekawan Institute Nusa Tenggara, 2025)
The integrated health posts (posyandu) in South Lembar Village, West Lombok Regency, face challenges in recording and reporting health data due to the low level of digital literacy among community health cadres, which slows down decision-making for village-level health programs. This community service initiative aims to enhance the competencies of cadres from 13 posyandu through the development of educational media in the form of Microsoft Excel tutorial videos, combined with in-person training sessions and field mentoring.The implementation methods included outreach activities, intensive training, the application of technology through short video tutorials on the TikTok platform, and evaluation using paired t-test analysis. The evaluation results indicated a significant improvement in cadre competencies, with the average pre-test score increasing from 62.00 to 90.00 in the post-test. Furthermore, the paired t-test results (p-value 0.045 < 0.05) demonstrate that the training had a positive impact on cadre skills.This improvement reflects the effectiveness of combining self-directed video learning with direct mentoring in accelerating mastery of basic Excel functions for managing nutrition, immunization, and maternal visit data. Overall, the program succeeded in strengthening the digital reporting system of the posyandu.